Education as a Determinant of Air Pollution Perception, Adaptation, and Perceived Health Outcomes in a Changing Climate - Aryal, Pitambar; Pandey, Chandra Lal; Poudyal, Amod Kumar (NPRC Journal of Multidisciplinary Research, 2026)
Introduction/Objectives: Climate change and air quality are interconnected, with the same sources of emissions and processes in the atmosphere leading to air pollutants both contributing to and reacting to changing climatic conditions. Emissions have been exacerbated by rapid urbanization, increased energy demand, and land-use changes, and climate-related factors, including increased temperatures, changes in precipitation, and extreme events, further exacerbate ambient air pollution, especially fine particulate matter (PM) and ozone. Evidence demonstrates that heat stress, extreme events, and high PM levels pose a high risk to population health, and thus integrated air quality management is necessary in conjunction with climate mitigation and adaptation. Climate change worsens health outcomes, such as respiratory and ocular morbidity, and places a burden on weak health systems, with low- and middle-income countries disproportionately impacted. Here, knowledge at the community level and locally based adaptation and risk reduction practices are crucial. Sarawal rural municipality is very susceptible to climate change and frequent climate-related disasters. It is thus important to understand how the community perceives the interface between climate change, air pollution, and health impacts. The study seeks to answer: How do communities perceive the interlinkages between climate change, climate-induced disasters, and air pollution? How do educational levels influence the perceptions of risk reduction and adaptation measures of individuals in the face of climate-induced disasters and air pollution? This paper explores perceptions, perceived drivers and community-based adaptation strategies to these risks.Methodology: The research was carried out in the Sarawal rural municipality, which included three wards (5, 6 and 7). Guided by a post positivist worldview, quantitative research design was used to examine comprehensive understanding of community perceptions and their experiences about climate change, air pollution and their impact on human health. Finite population correction formula was used to calculate the quantitative sample size; a total of 428 households were sampled through systematic random sampling.Results: A large majority of respondents, 276 (64.48%) out of 428 indicated that climate change causes air pollution whereas 335 (78.27 %) respondents opined that air pollution is a major respiratory health challenge. A total of 330 (77.10%) agreed that sustainable transportation reduces pollution; 383 (89.48%) respondents agreed & strongly agreed that mask use protects health. Respondents with no formal education consistently showed higher proportions of strong agreement e.g., 96 (67.13%) strongly agreed that climate change causes air pollution; 57 (39.86 %) strongly agreed on ventilation; 57 (39.86.0%) strongly agreed on sustainable transport. Respondents with formal education were more represented in neutral and moderate agreement categories e.g.,140 (49.12%) of neutral responses on ventilation and 70 (24.6%) on transport came from literate groups. All associations between education and perception were statistically significant (p < 0.05), chi-square tests affirm that there is a significant relationship between education and perceptions.Conclusion: The research shows that communities in Sarawal rural municipality are highly aware of the connections between climate change, air pollution, and health risks. Protective measures, such as mask use and risk reduction practices, are well-known, and experiential learning reinforces perceptions, proving the importance of community-based risk reduction, adaptation, and health promotion.Novelty: The paper is the first to combine the climate change-air pollution-health nexus using a community perception framework in rural communities of Nepal, where this type of analysis is scarce. It offers new evidence that experiential knowledge can be more important than formal education in the process of risk perceptions and adaptive responses.